Interleukin-1 Receptor 2: A New Biomarker for Sepsis Diagnosis and Gram-Negative/Gram-Positive Bacterial Differentiation - Lang, Yuejiao; Jiang, Yu; Gao, Min; Wang, Wenmei; Wang, Nian; Wang, Kangkai; Zhang, Huali; Chen, Guangwen; Liu, Ke; Liu, Meidong; Yang, Mingshi; Xiao, Xianzhong (Shock (Augusta, Ga.), 2017)
This study was undertaken to explore the value of interleukin-1 receptor 2 (IL1R2) as a novel potential biomarker for diagnosis of sepsis and discrimination of gram-negative (G)/gram-positive (G) bacterial sepsis. The study was performed in Kunming mice and septic patients. Inactive Escherichia coli or Staphylococcus aureus were used to stimulate Kunming mice (10 CFU/kg). In clinical study, septic patients with different pathogen infection were studied, and healthy volunteers and patients with systemic inflammatory response syndrome without definite infection were enrolled as control. IL1R2 transcriptions of human subjects' peripheral leukocytes were measured by real-time quantitative polymerase chain reaction assay. IL1R2 serum concentrations of mice and human subjects were measured by enzyme-linked immunosorbent assay. The value of IL1R2 as a biomarker was compared with procalcitonin (PCT), C-reactive protein (CRP), and Acute Physiology and Chronic Health Evaluation II (APACHE II). The results showed that IL1R2 expression was upregulated in mice treated with inactive Escherichia coli and septic patients. The elevation of serum IL1R2 was more significant in septic patients infected by Escherichia coli or G bacteria than in those infected by Staphylococcus aureus or G bacteria. For sepsis diagnosis and G/G bacterial sepsis discrimination, serum IL1R2 was more sensitive and specific than the traditional biomarkers such as PCT, CRP, and APACHE II as shown by the receiver operating characteristic curves. It was suggested that IL1R2 was a potential biomarker for diagnosis and G/G bacterial differentiation in sepsis.